Brazilian environmental justice in crisis: traditional peoples, environmental governance, and the limits of socioeconomic inclusion - Azenha, Gustavo S., author (Colorado State University. Libraries, 2017)
Through exploring the ongoing and intensified struggles between traditional peoples over land and natural resources in Brazil, I analyze the limitations of current forms of environmental decision-making and socioeconomic inclusion, and the contradictory impulses of sustainable development in which these are embedded. I examine the conjoined evolution of policies for economic development, the environment, and traditional rights since the 1980s in Brazil, exploring the shifting terrain of environmental justice struggles during different political economic phases, including democratization in the 1980s, the rise of neoliberalism in the 1990s, the postneoliberal turn of the early 2000s, and the current re-entrenchment of neoliberalism accompanying Brazil's political and economic crisis. Since the 1980s, there has been an overall trend towards strengthening socioenvironmental movements, policies, and governance, but in the last few years, there has been an erosion of traditional peoples' influence in environmental policies and an undermining of traditional land and resource rights. These trends occur alongside what have been seemingly contradictory efforts at promoting poverty alleviation and socioeconomic inclusion under the guise of sustainable development. I argue that these efforts are based on narrow conceptions of inclusion and citizenship that are modest in scope, focused on the short-term, and overlook critical structural matters. The promotion of socioeconomic inclusion has insufficiently safeguarded established rights and has limited participation in policymaking in important ways, yielding forms of sustainable development in which environmental and social concerns are superficial and echo historical exclusionary, assimilationist, and developmentalist efforts to promote "progress". With the strong conservative backlash of the current political and economic crisis, even these deficient efforts at socioeconomic inclusion are being scaled back, at the same time that environmental policies and traditional rights are being deeply eroded, posing serious challenges for cultivating a just and sustainable future. Because of the inseparable links between nature and state-making in Brazil, and the important role Brazil plays in international environmental governance, my analysis of contested ecologies in Brazil brings insights into the broader contradictions and limitations of global sustainable development efforts and the persistent challenges to cultivating more inclusive forms of environmental governance.
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: Brazil; environmental monitoring; sustainability; socioenvironmental challenges